Decrease in antigen‐specific CD63 basophil expression is associated with the development of tolerance to egg by SOTI in children. Issue 5 (19th May 2013) - Vila, Leticia; Moreno, Ana; Gamboa, Pedro M.; Martínez‐Aranguren, Rubén; Sanz, Maria L.
Abstract: Background: In the last decade, there have been an increasing number of studies on achieving tolerance to foods by specific oral tolerance induction (SOTI). Still, the underlying mechanism of SOTI is unknown. Our aim was to describe changes in CD63 expression on basophils following in vitro Ag‐specific stimulation by basophil activation test (BAT), after SOTI with egg in a pediatric population. Methods: Ten children with persistent allergy to egg were included. Skin prick tests (SPTs) and open food challenges (OFCs) were performed before SOTI. Specific IgE determination and BAT with egg white (EW), ovomucoid (OM), and ovalbumin (OVA) were performed before and after 1 month of the buildup phase of SOTI. Results: Total tolerance to egg was achieved in 9 cases and partial in one. After SOTI, there was a significant decrease in mean specific IgE levels (p < 0.05). CD63 expression also decreased (p < 0.05) in all patients. Conclusion: Decrease in Ag‐specific basophil responsiveness is associated with the development of clinical tolerance by SOTI. Abstract :